Association Between Self-rating Depression Scores and Total Ghrelin and Adipokine Serum Levels in a Large Population-Based Sample - Wittekind, Dirk Alexander; Kratzsch, Jürgen; Biemann, Ronald; Mergl, Roland; Riedel-Heller, Steffi; Witte, Veronika; Villringer, Arno; Kluge, Michael (Frontiers in Psychiatry, 2022)
Background: Ghrelin and the adipokines leptin and adiponectin have been suggested to be involved in mood and anxiety regulation and to be altered in affective disorders. However, studies investigating the association between ghrelin, leptin and adiponectin and depressive symptomatology are scarce but might contribute to a better understanding of their involvement in mood regulation. We thus aimed investigating the association between depressive symptomatology and total ghrelin as well as leptin and adiponectin serum levels in a large population-based sample. Methods: Total serum ghrelin, adiponectin and leptin levels were determined in 1666 subjects of a population-based cross-sectional study (‘LIFE’). The Center for Epidemiological Studies Depression Scale (CES-D) and the Inventory of Depressive Symptoms – Self Rating (IDS-SR) were administered. Multiple linear regression analyses were conducted to examine the association between total serum ghrelin, leptin and adiponectin and the intensity of depressive symptoms. Results: In the total sample (n=1092), neither ghrelin nor leptin or adiponectin serum levels showed a significant association with CES-D or IDS-SR sum scores in the total sample (N=1092) or in depressed/non-depressed subjects. Leptin serum levels showed a significantly positive association with IDS-SR sum scores in elderly men (60 years; β = 0.122, 95% CI: 0.009; 0.236; p = 0.035). Conclusion: Our study suggests that peripheral levels of ghrelin and adipokines in a cross-sectional study design might not be sufficient to measure their involvement in depression, suggesting that associations are more complex and multi-layered.